Moderate Drought Stress Induces Increased Foliar Dimethylsulphoniopropionate (DMSP) Concentration and Isoprene Emission in Two Contrasting Ecotypes of Arundo donax - Haworth, Matthew; Catola, Stefano; Marino, Giovanni; Brunetti, Cecilia; Michelozzi, Marco; Riggi, Ezio; Avola, Giovanni; Cosentino, Salvatore L.; Loreto, Francesco; Centritto, Mauro (Frontiers in Plant Science, 2017)
The function of dimethylsulphoniopropionate (DMSP) in plants is unclear. It has been proposed as an antioxidant, osmolyte and overflow for excess energy under stress conditions. The formation of DMSP is part of the methionine (MET) pathway that is involved in plant stress responses. We used a new analytical approach to accurately quantify the changes in DMSP concentration that occurred in two ecotypes of the biomass crop Arundo donax subject to moderate drought stress under field conditions. The ecotypes of A. donax were from a hot semi-arid habitat in Morocco and a warm-humid environment in Central Italy. The Moroccan ecotype showed more pronounced reductions in photosynthesis, stomatal conductance and photochemical electron transport than the Italian ecotype. An increase in isoprene emission occurred in both ecotypes alongside enhanced foliar concentrations of DMSP, indicative of a protective function of these two metabolites in the amelioration of the deleterious effects of excess energy and oxidative stress. This is consistent with the modification of carbon within the methyl-erythriol (MEP) and MET pathways responsible for increased synthesis of isoprene and DMSP under moderate drought. The results of this study indicate that DMSP is an important adaptive component of the stress response regulated via the MET pathway in A. donax. Moreover, DMSP is likely a multifunctional molecule playing a number of roles in the response of A. donax to reduced water availability.